Infective Endocarditis in Children as an Increasing Clinical Problem—A Case Series - Urszula Abramczyk; Paweł Cześniewicz; Jacek Kusa (Children, 2024)
In September 2023, the European Society of Cardiology (ESC) published new guidelines for the management of endocarditis. Infective endocarditis (IE) remains a significant life-threatening disease, concerning an increasingly younger age group, especially children with congenital heart disease (CHD) and young adults after multiple cardiac surgeries. This study’s aim was to alert the medical community to the problem of increasing IE case numbers and IE course complexity. Of the eight patients who suffered from IE treated in 2023 in our department, we describe the four whose course was the most extraordinary. Afterward, we compared the number of IE patients treated over the years in our department. All cases described children with congenital heart disease suffering from IE. The IE clinical presentation in all patients was extremely diverse, necessitating the utilization of all available diagnostic methods. Each child underwent specialized treatment and subsequently qualified for cardiac surgery. While the etiology and treatment of IE are well established, it remains a formidable challenge for physicians. Pediatric patients who have undergone multiple cardiac surgeries constitute a steadily expanding group and are especially susceptible to IE throughout their lives. Currently, no recommendations exist for the management of endocarditis in pediatric patients. This gap compels pediatricians to adapt existing guidelines designed for adult patients and to rely on scientific reports, such as case studies.